A Novel Encryption Frame for Medical Image with Watermark Based on Hyperchaotic System. (9th April 2014) - Zhang, Shun; Gao, Tiegang; Gao, Lin
Abstract : An encryption frame of medical image with watermark based on hyperchaotic system is proposed in this paper. Medical information, such as the patients' private information, data needed for diagnosis, and information for authentication or protection of medical files, is embedded into the regions of interest (ROI) in medical images with a high capacity difference-histogram-based reversible data-hiding scheme. After that, the watermarked medical images are encrypted with hyperchaotic systems. In the receiving end, the receiver with encryption key can decrypt the image to get similar images for diagnosis. If the receiver has the key for data hiding at the same time, he/she can extract the embedded private information and reversibly recover the original medical image. Experiments and analyses demonstrate that high embedding capacity and low distortion have been achieved in the process of data hiding, and, at the same time, high security has been acquired in the encryption phase.